Double valve involvement: papillary fibroelastoma in a patient with severe mitral and aortic valve regurgitation. Issue 7 (16th July 2020) - Ajiboye, Oyintayo; Racoma, Jan Michael; Hussain, Kifah; Mba, Benjamin
Abstract : Cardiac papillary fibroelastoma is a benign neoplasm that arises in the endocardium. It commonly presents as an incidental finding on transthoracic echocardiography or as emboli to the coronary, cerebral or pulmonary vasculature. Clinical manifestations described in the literature have generally been related to a sequelae of the associated embolic phenomenon of these lesions. Valve regurgitation is less common with papillary fibroelastoma and when found, it is not known to cause severe regurgitation requiring valve replacement. We report a case of papillary fibroelastoma in a patient with severe mitral and aortic valve regurgitation in association with mobile masses requiring double valve replacement. This patient managed initially as infective endocarditis with severe double valve regurgitation, was found to have valvular masses concernng for papillary fibroelastoma and subsequently confirmed on pathology.